Musical metaphors in the poetry of Wallace Stevens - Kennedy, Victor (ELOPE (Ljubljana), 2016)
Wallace Stevens's "The Man with the Blue Guitar" (1937) is widely recognized as one of the most important and influential poems of the 20th century. Inspired by Picasso's painting The Old Guitarist, the poem in turn inspired Michael Tippett's sonata for solo guitar, "The Blue Guitar" (Tippett 1983) and David Hockney's The Blue Guitar: Etchings by David Hockney who was inspired by Wallace Stevens who was inspired by Pablo Picasso (Hockney and Stevens 1977). Central to "The Man with the Blue Guitar," the metaphor of the musical instrument as a transformational symbol of the imagination is common in Stevens's poems. The structure of "The Man with the Blue Guitar," according to J. Hillis Miller, is the structure of stream-of-consciousness. Stevens's poem creates what has been called "the deconstructed moment in modern poetry," "an attempt to project a spatialized time that can be viewed from the privileged position of a timeless, static moment capable of encompassing a life at a glance" (Jackson 1982). This consciousness, which Derrida refers to as the "trace," Stevens calls "the evasive movement of language." The trace is the perception of the absence of meaning after the word or perception has passed, the glimpse of a hidden meaning that immediately vanishes. Stevens's poem influenced not only other poets, artists and composers; references to and echoes of his ideas and techniques can be seen in popular music and culture well into the 21st century.
Keywords: eksfraza; glasbene metafore; literarne študije; Stevens, Wallace: The Man with the Blue Guitar